Medidas para reducción de huella de carbono energético en proceso de pasteurización de una empresa láctea en Bogotá (2019)
Summary In the present investigation, the formulation of some measurements for reducing energy carbon footprint generated by the equipment used in the pasteurization process in a dairy company in Bogotá is proposed. To achieve this objective, a descriptive level research with design was carried out. field in the selected company, through the data collection process proposed by the PIGA methodology based on the GHG Protocol (Greenhouse Gas Protocol), which is an international standard for measuring greenhouse gases.